The Methods of Selection of the Project Management Methodology - Kononenko, Igor; Kharazii, Anna (Тернопільський національний економічний університет, 2014)
The problem of selecting the methodology to manage the company's projects or a specific project is reviewed. The authors suggest the methods to select methodology that are designated for application under the conditions of different degrees of awareness of the decision-maker about the existing methodologies, their advantages and weaknesses, about the range of efficient use. As the methods are more precise, so they require a more laborious analysis of the project and its environment. It is proposed to make the most substantiated choice resulting from solution of the task on optimizing the project's scope to the following criteria: profit, time, cost, quality, risk, and in terms of the company's maturity growth.
Keywords: project management; selection; methodology; optimization; profit; cost; maturity